Smooth Crossing of wΛ=−1 Line in a Single Scalar Field Model - Abhik Kumar Sanyal (Advances in High Energy Physics)
Smooth double crossing of the phantom divide line wΛ=−1 has been found possible with a single minimally coupled scalar field for the most simple form of generalized k-essence cosmological model, in the presence of background cold dark matter. Such crossing is a sufficiently late time transient phenomenon and does not have any pathological behaviour.